ANALISIS SISTEM PENGAWASAN KERJA PADA PT. TRIMITRA SWADAYA MEDAN - Nike Arnita; Teuku Fahmi (Jurnal Ilmu Sosial Dan Politik, 2022)
The purpose of this research is to find out whether the implementation of the supervisory system results in a sense of responsibility towards work that is also not maximized at PT Trimitra Swadaya Medan, to find out the ability of the existing supervisory system to minimize and anticipate work constraints that occur at PT Trimitra Swadaya Medan and to determine the ability of the existing performance monitoring system in the company to support the maximum increase in employee performance at PT Trimitra Swadaya Medan. Research uses data collection techniques of observation, interviews, observation and documentation studies. The data analysis technique is descriptive analysis method. Based on the research results, it is known that work supervision at PT. Trimitra Swadaya Medan is known to have a tendency to not apply the supervisory system optimally from the leadership so that employees' sense of responsibility towards work also tends to be less than optimal. In addition to supervising the work of employees in order to maintain work discipline so that it always goes according to regulations and procedures, it is necessary to have supervision from those who also have general knowledge in the field of management, especially organizational management. Furthermore, the constraints on work supervision state that one of the supervisor's obligations is to review all employee activities as well as the supervisor's efforts in supervising employee performance. Basically, the supervisory system is divided into two, namely general supervision and special supervision.